2005
DOI: 10.1080/08035320510028139
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic profile of recombinant human N-acetylgalactosamine 4-sulphatase enzyme replacement therapy in patients with mucopolysaccharidosis VI (Maroteaux–Lamy syndrome): a phase I/II study

Abstract: Aim: Mucopolysaccharidosis VI (Maroteaux-Lamy syndrome) is a lysosomal storage disease caused by a deficiency of the enzyme N-acetylgalactosamine 4-sulphatase (ASB). Enzyme replacement therapy with recombinant human ASB (rhASB) has been studied in a randomized, double-blind, two-dose (0.2 and 1.0 mg/kg/week) phase I/II study (n=7) followed by an open-label single dose (1.0 mg/kg/week) extension study. We report the pharmacokinetic profile of rhASB and the impact of antibody development. Methods: Pharmacokineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 10 publications
1
17
0
5
Order By: Relevance
“…Rare lysosomal storage disorders, such as mucopolysaccharidosis I (MPS I, Hurler syndrome), MPS VI (Maroteaux-Lamy syndrome), Gaucher disease, and Fabry disease are currently treated by intravenous enzyme replacement therapy [10][11][12][13][14][15][16]. Enzyme replacement therapy has successfully treated some aspects of the physical disease in MPS patients and has been well tolerated.…”
Section: Introductionmentioning
confidence: 99%
“…Rare lysosomal storage disorders, such as mucopolysaccharidosis I (MPS I, Hurler syndrome), MPS VI (Maroteaux-Lamy syndrome), Gaucher disease, and Fabry disease are currently treated by intravenous enzyme replacement therapy [10][11][12][13][14][15][16]. Enzyme replacement therapy has successfully treated some aspects of the physical disease in MPS patients and has been well tolerated.…”
Section: Introductionmentioning
confidence: 99%
“…Não encontramos na literatura quais seriam os valores considerados clinicamente relevantes, mas alguns autores, avaliando MPS VI, consideram arbitrariamente o aumento superior a 10 o como significativo 25,26 . Portanto, houve mudanças clinicamente relevantes na mobilidade articular do cotovelo (diferença média não relatada) 13 , ombro (aproximadamente 12 o , abdução, flexão-extensão) 16 e quadril (aproximadamente 14 o , flexão), este último avaliado apenas por um pequeno estudo (n = 10 pacientes) 15 .…”
Section: Discussionunclassified
“…Patients suffer from growth retardation as well as from bone and joint changes, hepatosplenomegaly, enlargement of heart valves, and cardiomyopathy. A recombinant arylsulfatase B (galsulfase) [56] was approved in 2005 for treatment of this inborn error of metabolism. Clinical trials have demonstrated that Naglazyme provides clinically important benefits for MPS VI patients, specifically improved endurance.…”
Section: Glycosidasesmentioning
confidence: 99%